Studi Eksperimental Karakteristik Beton Mutu Tinggi dengan Memanfaatkan Limbah Fly Ash dan Coco Fiber - Alvanda, Muhammad Reyhan; Suhelmidawati, Etri; Tiara, Tiara; Putri, Casy Almia; Akbar, Hikmal; Syauqi, Hafizhan; Satwarnirat, Satwarnirat (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
The issue of environmental friendliness has become very popular recently. Various industrial sectors must pay attention to environmental factors as a global sustainability goal. In the construction industry sector, concrete is a much-needed material in making building structures. Concrete becomes environmentally friendly by utilizing waste as a substitute for some of the ingredients. This research uses fly ash and coconut fiber. This study aims to determine the effect of renewable innovation in the addition of fly ash and coco fiber waste on the value of compressive strength and flexural strength of concrete and to determine the composition of the most optimum percentage of waste addition, as well as the resulting crack pattern. This research uses the international standard ACI 211.4R-93, which is an experiment with the addition of 15% fly ash and variations in the addition of coconut fiber 0.5%, 1%, 1.5%, and 2%. The concrete quality planning in this study is 40 MPa with concrete treatment for 28 days and 56 days. This test uses cylindrical test objects (15cm x 30cm) with a total of 30 samples for compressive strength testing and beams (60cm x 15cm x 15cm) with a total of 30 samples for flexural strength testing. The results obtained in this study are the optimum compressive strength found in the variation of adding 1.5% fiber and 15% fly ash at 56 days of concrete age of 33.12 MPa. The highest concrete flexural strength value is found in the 2% fiber addition variation.